MICROSCOPE ON THE USAGE TRAINING AS A FORM FOR ACHIEVING SDGS FOR HIGH SCHOOL STUDENTS IN INDONESIA - Anindita, Reza; Nathalia, Dede Dwi; Beandrade, Maya Uzia; Putri, Intan Kurnia (LP2M Universitas Ibrahimy, 2025)
One of the instruments that is often not available for cell observation skills in high schools in Bekasi City is a microscope. Therefore, it is necessary to carry out community service activities (CSA) in the form of training in the use and maintenance of microscopes, making and observing cell slides, and cell observation documentation techniques for high school students in Bekasi City. This CSA method, based on Asset-Based Community Development (ABCD) and Participatory Action Research (PAR), involves planning integrated CSA programs offered to several high schools in Bekasi City. The implementation stage was carried out in 6 meetings (each meeting started from 08.00-16.00) by providing a pre-test, delivering materials, conducting a post-test, practicing microscope use, making and observing cell slides, and documenting cell slide techniques. The evaluation stage was carried out by processing qualitative and quantitative data. The results of this CSA include 30 students: 19 from Al-Muhtadin High School and 11 from Annida Al-Islamy, MA. Statistical analysis using paired t-tests produced a sig value. 0.01<0.05 or CS activities can significantly increase the average value of knowledge about microscopes, while the average value of the skills test is 76.92. This CSA concludes that providing microscope materials and training as a CS activity package can enhance the knowledge and skills of 19 Al-Muhtadin High School students and 11 Annida Al-Islamy MA students in observing cells using a light microscope.